2020
DOI: 10.1002/macp.202070025
|View full text |Cite
|
Sign up to set email alerts
|

Triblock Copolymers Based on Sucrose Methacrylate and Methyl Methacrylate: RAFT Polymerization and Self‐Assembly

Abstract: Front Cover: In article number 1900561 by Maria Isabel Felisberti and co‐workers, ABA and BAB triblock amphiphilic copolymers based on sucrose methacrylate, a monomer obtained from a renewable source, are synthesized by reversible addition–fragmentation chain transfer polymerization. They are capable of self‐assembly in solution, forming aggregates, whose morphologies depend on the composition, molar mass, and architecture of the copolymers, and are capable of stabilizing water–oil emulsions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…[ 36 ] Drug delivery experiments conducted using P(SMA‐ ran ‐NIPAAm) hydrogels loaded with diclofenac sodium and bovine serum albumin as model drugs showed that the drug release rate may be controlled by the network composition and hydrophilicity and molecule size. Di‐ and triblock copolymers based on SMA and methacrylates [ 37–39 ] presented a low water swelling coefficient due to the self‐assembly ability of these copolymers in solid, forming lamellar structures. [ 37 ] In aqueous media, these copolymers self‐assembled in aggregates and vesicles, and no hydrogel was formed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 36 ] Drug delivery experiments conducted using P(SMA‐ ran ‐NIPAAm) hydrogels loaded with diclofenac sodium and bovine serum albumin as model drugs showed that the drug release rate may be controlled by the network composition and hydrophilicity and molecule size. Di‐ and triblock copolymers based on SMA and methacrylates [ 37–39 ] presented a low water swelling coefficient due to the self‐assembly ability of these copolymers in solid, forming lamellar structures. [ 37 ] In aqueous media, these copolymers self‐assembled in aggregates and vesicles, and no hydrogel was formed.…”
Section: Introductionmentioning
confidence: 99%
“…[ 37 ] In aqueous media, these copolymers self‐assembled in aggregates and vesicles, and no hydrogel was formed. [ 38,39 ] Therefore, the random copolymerization of SMA with other monomers seems to be more appropriate to produce hydrogels with high swelling coefficients.…”
Section: Introductionmentioning
confidence: 99%
“…[ 33–37 ] The polymer structure control for methyl methacrylate (MMA) and other many kinds of conjugated monomers were performed using trithiocarbonate compounds as the RAFT agent. [ 38–43 ] In many cases, however, it has been reported that the precise control of the living radical polymerization is interfered by polar and functional groups included in the methacrylate monomers, such as HEMA. [ 44–50 ] In this study, therefore, we synthesized PBHEMA with well‐controlled molecular weight, molecular weight distribution, and chain end groups as well as the block copolymers containing PBHEMA and the other polymethacrylate segments using the RAFT polymerization process using 4‐cyano‐4‐((dodecylsulfanylthiocarbonyl)sulfanyl)pentanoic acid (CDTPA) as the RAFT agent ( Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Os espectros de 1 H RMN para ambos os copolímeros também foram obtidos em D2O (Figuras 17b e 17d), o que revelou a supressão dos sinais dos hidrogênios do bloco P4VP, indicando que estes copolímeros se auto-organizam em meio aquoso em estruturas core-shell 52 . polimerização RAFT resulta no crescimento das cadeias de ambos os lados do CTA, o que pode resultar em uma distribuição de massa molar mais larga, como reportado na polimerização RAFT de monômeros acrílicos 18 , metacrílicos 131,151 e acrilamidas 152 .…”
Section: Comportamento Em Solução Do Homopolímero Poeg5maunclassified